Early Rate of Revision of Total Hip Arthroplasty Related to Surgical Approach: An Analysis of 122, 345 Primary Total Hip Arthroplasties. (4th November 2020) - Hoskins, Wayne; Bingham, Roger; Lorimer, Michelle; Hatton, Alesha; de Steiger, Richard N.
Abstract : Background: A number of surgical approaches are available for total hip arthroplasty (THA), but there are limited large-volume, multi-surgeon data comparing the rates of early revisions following these approaches. The aim of this study was to compare the rate of revision of primary conventional THA related to surgical approach. Methods: Data from the Australian Orthopaedic Association National Joint Replacement Registry were analyzed for all patients who had undergone a primary THA for osteoarthritis from January 2015 to December 2018. The primary outcome measure was the cumulative percent revision (CPR) for all causes. Secondary outcome measures were major revision (a revision procedure requiring change of the acetabular and/or femoral component) and revision for specific diagnoses: fracture, component loosening, infection, and dislocation. Age, sex, body mass index (BMI), American Society of Anesthesiologists (ASA) score, femoral head size, and femoral fixation were assessed as potential confounders. Results: There was a total of 122, 345 primary conventional THAs for which the surgical approach was recorded in the registry; 65, 791 were posterior, 24, 468 were lateral, and 32, 086 were anterior. There was no difference in the overall CPR among approaches, but the anterior approach was associated with a higher rate of major revisions. There were differences among the approaches with regard to the types of revision. When adjusted for age, sex, ASA score, BMI, femoral head size, and femoral fixation, the anterior approach was associated with a higher rate of femoral complications—i.e., revision for periprosthetic fracture and femoral loosening. There was a lower rate of revision for infection after the anterior approach compared with the posterior approach in the entire period, and compared with the lateral approach in the first 3 months. The posterior approach was associated with a higher rate of revision for dislocation compared with both the anterior and the lateral approach in all time periods. The anterior approach was associated with a lower rate of revision compared with the lateral approach in the first 6 months only. Conclusions: There was no difference in the overall early CPR among the surgical approaches, but the anterior approach was associated with a higher rate of early major revisions and femoral complications (revisions for periprosthetic fracture and femoral loosening) compared with the posterior and lateral approaches and with a lower rate of dislocation and infection. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.